Treatment of Crimean-Congo hemorrhagic fever - (:unkn) unknown (Springer Netherlands, 2007)
Ribavirin is a synthetic purine nucleoside analog with a modified base and D-ribose sugar, also known as virazol, first synthesized by Sidwell and colleagues in 1972 [43, 49] (Fig. 19-1). It is of particular interest, because it was the first synthetic nucleoside to exhibit broad spectrum antiviral activity, and it is one of few antiviral drugs in clinical use effective against agents other than HIV and herpesviruses [43]. It inhibits the replication of a wide range of RNA and DNA viruses in vitro, including orthomyxo, paramyxo, arena, bunya, flavi, herpes, adeno, pox, and retroviruses [49]. In current clinical practice, ribavirin is commonly used for certain viral infections (Table 19-1). Most notably, it is used in combination with interferon-α for treatment of HCV infection [66]. Ribavirin aerosol is used for treatment of pediatric infection by respiratory syncytial virus [19]. It is the only antiviral drug that could be also used in viral hemorrhagic fever syndromes. Besides Crimean- Congo hemorrhagic fever (CCHF), it is used in Lassa fever [70]. Viruses in the Bunyaviridae family are generally sensitive to ribavirin [92]. A prospective, randomized, double-blind, placebo-controlled trial of 242 patients with serologically confirmed Hantaan virus in the People's Republic of China found a sevenfold decrease in mortality among ribavirin-treated patients [54], other studies did not confirm these benefits. Ribavirin was found to be effective against CCHF virus (CCHFV) in vitro [99, 104]. © 2007 Springer Netherlands. All rights reserved.